CREATING A TOURIST PRODUCT FOR THE SAMARKAND REGION - Abdalimova D. M.; Tursunova G. R. (Bright Mind Publishing, 2026)
This article examines the issues of creating competitive tourism products based on the rich historical, cultural, and natural potential of the Samarkand region. The study analyzes the region’s tourism resources, infrastructure capacity, and service sector, and considers ways of developing tourism products in line with modern market requirements. In addition, practical recommendations are proposed for designing innovative tourism products for the Samarkand region, taking into account the needs of domestic and international tourists.
Keywords: Tourism product, tourism resources, infrastructure, service sector.